IMMUNOHISTOCHEMICAL PROFILE OF BREAST CANCER SUBTYPES IN PATIENTS SEEN AT NAPOLEÃO LAUREANO HOSPITAL, PARAÍBA, BRAZIL - Pinheiro, Jader Bruno Formiga; Torres, Adriana de Freitas; Paz, Alexandre Rolim da (Mastology, 2019)
Objective: To determine the profile of molecular subtypes of invasive breast carcinomas among women who underwent immunohistochemical study from May 2013 to December 2014, at Hospital Napoleon Laureano, Paraiba, Brazil, to characterize the mean age at diagnosis and describe the percentage of the following variables: estrogen and progesterone receptors, human epidermal growth factor 2 and proliferation index (Ki-67). Method: retrospective ecological study using the secondary databases at Hospital Napoleon Laureano Pathology Laboratory. The population consisted of 683 cases of invasive breast carcinoma with immunohistochemical study in this institution between May 2013 and December 2014. Results: Of the 683 patients, 46 were excluded because they presented inconclusive results for human epidermal growth factor 2 (++), totaling 637 recorded cases. Five hundred and fifty-six (87.28%) were 40 or older, and 81 (12.72%) under 40 years old. As for estrogen and progesterone receptor, 452 patients (70.96%) were positive for both receptors, while 185 (29.04%) showed no positivity. Four hundred and sixty-eight women (73.47%) did not show overexpressed human epidermal growth factor 2, while 169 (26.53%) did. The percentage of Ki-67 showed 474 individuals (74.41%) with a high proliferation index and 163 (25.59%) with a low index. The molecular subtypes showed the following prevalence: luminal A (143 cases; 22.45%), luminal B (250 cases; 39.25%), luminal B-enriched (113 cases; 17.84%), HER2 (57 cases; 8.95%) and triple-negative (74 cases; 11.62%). Conclusion: This study supported the notion of regional differences in the profile of breast tumors, since it showed a greater prevalence of triple-positive carcinomas and lower frequency of triple-negative tumors compared to studies of other Brazilian regions.